Non-uniform dispersion of toughening agents and its influence on the mechanical properties of polypropylene - Q. Fu; Z. Li; C. M. Liu; H. L. Liu; K. Wang (eXPRESS Polymer Letters)
To achieve excellent properties of polymer blends and composites, good dispersion and uniform distribution of second component or filler in the matrix are often required. However, more and more evidences reveal that uniform distribution is not always the best. To further prove this idea, in this work, we purposely designed and prepared different samples of isotactic polypropylene (iPP)/elastomer or iPP/β-nucleating agent with uniform and non-uniform distribution of the modifiers via stacking the blending sheets in different sequence. It was found that for a given amount of toughening agent, the impact strength of polymer blends with non-uniform distribution of elastomer or β-nucleating agent could be much higher than its uniformly dispersed counterpart, while the tensile strength and tensile modulus remain relatively constant. The instrumented impact test confirmed that among the samples with different layered structures, the absorbed energy during crack initiation differs little from each other. Whereas absorbed energy during crack propagation process shows the same trend as final impact strength, making it the controlling parameter during the impact process. When cracks are initiated at higher toughening agents content side, the relatively smooth fracture surfaces near the crack edge area proved that they absorb small energy and the adjacent inner part showed obviously plastic deformation, corresponding to higher energy absorption. Our work demonstrates again that design and control of the hierarchical structure of polymer articles is vital for high performance properties and non-uniform distribution of filler could be much better than the uniform distribution.